Optimalisasi Manajemen Perubahan Dalam Mewujudkan Pembangunan Zona Integritas Menuju WBK/WBBM: Studi Pada Lapas Kelas IIB Ciamis - Asep Deni Wahyudi; Enas Enas; Oyon Saryono (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2024)
The failure to realize the development of an Integrity Zone towards WBK/WBBM is due to the lack of systematic and consistent changes in mindset and work culture. This failure is due to the fact that effective work mechanisms have not been formed, the mindset of employees in public services has not been formed, and leaders have not optimally provided influence as role models. Relevant theory as stipulated in Permenpan RB Number 90 of 2021. The research method uses descriptive qualitative research methods. Research results (1) The involvement of all employees is very important because it shows commitment and responsibility in developing the Integrity Zone (2) Asepk of Change Management is collective work and high commitment from employees. (3) Optimizing Change Management, including establishing changes in mindset and work culture, in the leadership change agenda as role models have high optimism. (4) Controlling resistance to change requires strategic efforts to handle it.